2017
DOI: 10.3390/su9091541
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Spatial Structures of Regional City Networks from Expressway Traffic Flow Data: A Case Study from Jiangsu Province, China

Abstract: On the basis of the "space of flows" theory, city networks emphasizing factor connectivity and spatial connection have become a core perspective for regional spatial relationships. They provide a context for discussing the spatial structures of city networks and a scientific basis for making regional development policies. Relying on expressway traffic flow data from Jiangsu Province in 2014, this study describes macro-spatial patterns and hierarchical structures of city networks, and uses the Walktrap algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…In terms of geographical distribution, until March 18, the cumulative number of confirmed patients in Nanjing, Xuzhou, and Suzhou ranked the top three in Jiangsu. According to the transportation network map of Jiangsu Province (Figure 1D), Nanjing and Xuzhou are the largest road or railway transportation hub in Jiangsu province, and Suzhou has extremely convenient railway and road traffic with Shanghai, the international transportation hub [14,15]. The above data suggested that the transportation convenience of the region was relative to the number of imported cases.…”
Section: Discussionmentioning
confidence: 96%
“…In terms of geographical distribution, until March 18, the cumulative number of confirmed patients in Nanjing, Xuzhou, and Suzhou ranked the top three in Jiangsu. According to the transportation network map of Jiangsu Province (Figure 1D), Nanjing and Xuzhou are the largest road or railway transportation hub in Jiangsu province, and Suzhou has extremely convenient railway and road traffic with Shanghai, the international transportation hub [14,15]. The above data suggested that the transportation convenience of the region was relative to the number of imported cases.…”
Section: Discussionmentioning
confidence: 96%
“…The main characteristics of today's cities are mobility and connection (Shen & Gu, 2009), and the city network structure has gradually become an important form of regional and even national spatial organization. The academic community has studied city networks for a long time, and relevant research mainly involves “enterprise associations” (Dong & Zhen, 2013; Wu & Ning, 2012; Ye, Cao, Wang, & Wu, 2017; Zhuang, Yang, Jin, & Han, 2017), “traffic links” (Derudder & Witlox, 2005; Jin, 2001; Ke, 2015; Ke, Chen, & Yu, 2017; Zhang, Hao, Ji, & Liu, 2019), and “information link” (Cao, Zeng, & Ye, 2019; Jiang, Sun, & Ren, 2015; Tranos & Gillespie, 2009; Zhen, Wang, & Chen, 2012). As the most important entities in the economy, enterprises can expand their scale through mergers and acquisitions and self‐investment in order to achieve economies of scale.…”
Section: Introductionmentioning
confidence: 99%
“…Data on passenger air and railway flow are easy to obtain and have great advantages in large-scale network research, but there are considerable limitations on urban connection research in smaller areas. To better study urban linkages at a smaller scale, highway passenger flow has become widely used as an alternative to air and rail flow [10,11]. The related research enriches the empirical cases of different traffic flows for urban network systems of different scales to some extent and analyzes the basic characteristics of the spatial structure, network association and hierarchical structure of regional connections.…”
Section: Introductionmentioning
confidence: 99%